Retórica poética e erotismo no último Dalton Trevisan - Martins, Alexandre Gaioto (2014)
This thesis is committed to analyse part of the poetical rhetoric from Dalton Trevisan's work, especially its erotic-theme manifestations, aiming to understand, throughout the largest inflow of its poetic nature, the assertion of a new creative period from the Curitiba-native fiction writer, established with Ah, é? (1994), collection considered by many critics as a breakthrough of its work due to the more intensive presence of its poetical literacy and variety of styles, such as the epigram, the haiku. Yet 234 (1997), part of this period within the same minimalist purpose from Ah, é?; and the anthology Novos contos eróticos (2013), which gather erotic-theme tales carved in Capitu sou eu (2003), Rita Ritinha Ritona (2005), Macho não ganha flor (2006), O maníaco do olho verde (2008), Violetas e pavões (2009) e O anão e a ninfeta (2011). Search for recognise in this texts the speech-structure reorientation by bringing awareness to its ostensive poetic-nature, that are resumed theoretical studies (poetic style), among others, Aguiar e Silva, Massaud Moisés and Alfredo Bosi, beyond eroticism assessments of Georges Bataille e Jean Baudrillard. Notwithstanding this thesis assess the ironic articulation of erotic tales with the technical background from, among others, Linda Hutcheon. Last but not least, this work also aim to consider the double stylistic operation (poetry and irony) from erotic rhetoric, further from the initial categorical fusion (prose/poetry).